2007
DOI: 10.1007/s10672-007-9046-y
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Factors Affecting Quality of Work Life and Career Attitudes of Gay Men

Abstract: With the current political environment (such as new legislation recognising gay and lesbian couples) and societal changes (such as increasing disclosure of sexual identity in the workplace) in countries such as the USA and Australia, organizations are increasingly recognising the existence of their gay and lesbian employees. This paper reports on an on-line survey of 581 working gay men, examining their quality of work life and career attitudes. The findings of the research provide a strong indication that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
0
38
0
1
Order By: Relevance
“…This period often coincides with adolescence-the developmental stage when one evaluates academic and career directions. At the same time, the inclination of gay men and lesbians to pursue nontraditional occupations (Chung, 1995) may conflict with the gender-role expectations imposed by the society, due to which gay men and lesbians may not enjoy the support and activities that heterosexuals do (Trau & Härtel, 2002). Those who pursue a nontraditional career are often devalued or stigmatized.…”
Section: H1mentioning
confidence: 99%
“…This period often coincides with adolescence-the developmental stage when one evaluates academic and career directions. At the same time, the inclination of gay men and lesbians to pursue nontraditional occupations (Chung, 1995) may conflict with the gender-role expectations imposed by the society, due to which gay men and lesbians may not enjoy the support and activities that heterosexuals do (Trau & Härtel, 2002). Those who pursue a nontraditional career are often devalued or stigmatized.…”
Section: H1mentioning
confidence: 99%
“…Being devalued by others on the basis of group membership leads to emotional distress for the stigmatized person, and this may subsequently lead to negative attitudes toward the people and the environment in which the individual with an invisible stigma is embedded (Major & O'Brien, ). Indeed, self‐reported studies on lesbian and gay workers with an invisible stigmatized identity consistently show that the feelings of being discriminated against in organizational contexts are linked to negative work‐related outcomes (Button, ; Day & Schoenrade, ; Griffith & Hebl, ; Ragins & Cornwell, ; Trau & Härtel, ). For this invisible stigmatized group, it also has been found that support from the organization (Griffith & Hebl, ; Trau & Härtel, ), supervisor (Huffman et al, ), and coworkers (Ragins et al, ) is positively related to job satisfaction.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…For example, the organization might publicize its inclusive stance toward neurodiversity in newsletters and via its intranet and provide information on who neuro-atypical employees may contact to safely and confidentially disclose their diagnosis and receive the support required to perform their work. Although not including studying people with autism, research indicates that self-disclosure of an invisible identity is associated with higher self-ratings of quality of work life and more positive attitudes toward one's job and employer (Trau & Härtel, 2007). Future research needs to investigate the generalizability of these findings.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%